Pengembangan Media Animasi Larutan Penyangga dalam Model Pembelajaran Berbasis Masalah Ditinjau dari Motivasi dan Hasil Belajar Peserta Didik Kelas XI IPA SMAN 5 Makassar - Almur, Faathir; Sulastry, Taty; Wijaya, Muhammad (Program Pasca Sarjana UNM, 2023)
This study is a development research that aims to develop buffer solution animation media in a problem-based learning model based on learning motivation and learning outcomes that are valid, practical, and effective to be used. The development model used in this study consisted of the needs analysis stage, the design stage, the development and implementation stages. The buffer solution animation media that had been developed had gone through the validation stage by the assessors and had gone through the trial stage to produce a valid, practical, and effective learning media. The results of the study show that the buffer solution animation media developed has: (1) expert validation of media 4.00 with very valid criteria, and (2) validation of material expert 3.23 with valid criteria. The buffer solution animation media is stated to be practical and effective because the practicality test related to (1) its implementation in problem-based learning model is at an average value of M = 1.87 in the category (1.5 ≤ M ≤ 2.0), which means that the aspects and criteria observed are in fully implemented category, (2) the teacher's response is very positive with a percentage of 87.50% with very practical criteria, and (3) positive response of students with 80.03% with very practical criteria. The buffer solution animation media also meets the effective criteria with the results: (1) the students' learning motivation has increased from 69.48% to 77.83% which is in high category, (2) the students' learning activities meet the criteria for being very active with an average of 89.28%, and (3) the learning outcomes meet the criteria for classical completeness (≥85%) with an average percentage of 86%.